X-Band Nanosecond Microwave Gunn Generator; 16th Symposium on High Current Electronics, September 19-24, 2010 - Klimov A. I. Aleksey Ivanovich; Gubanov V. P. Vladimir Petrovich; Koval'chuk O. B. Oleg Borisovich; Konev V. Yu. Vladimir Yurievich; Rostov V. V. Vladislav Vladimirovich (High Pover Microwaves, 2010)
Title screen